Implementation of Therapeutic Group Therapy (TKT) for School Age Children and Self Help Group (SHG) for Public Elementary School Students in Harjosari Village, Pekanbaru: Penerapan Terapi Kelompok Terapeutik (TKT) Anak Usia Sekolah dan Self Help Group (SHG) pada Siswa Sekolah Dasar Negeri di Kelurahan Harjosari Pekanbaru - Usraleli, Usraleli; Ira Oktaviani; Wiwiek Delvira; Alkausyari, Alkausyari (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Problems that often occur in elementary school students related to growth and development include: frequent daydreaming, feelings of inferiority, frequent dependence on friends, difficulty adjusting to classmates, frequent complaints, jealousy, often alone, cheating, difficulty in capturing school lessons, making noise in class. Symptoms of this behavior are the result of misparenting in the family, differences in educational, socioeconomic backgrounds and deviations in the child's personality. From the school side, this problem arises because of the mistakes and weaknesses of teachers in treating children or the lack of teacher ability to deal with large numbers of students as found in government elementary schools such as only public elementary schools in Harjosari Village, Pekanbaru City. This community service activity is one of the efforts to realize the Tri Dharma of higher education. The purpose of this community service is to find out how the application of Therapeutic Group Therapy (TKT) for school-age children in grade III students. This community service activity is planned to be held at SD Negeri in Kelurahan, Kelurahan Delima, Tampan District, Pekanbaru from February to September 2023 (8 Months). This service activity is in the form of applying Therapeutic Group Therapy and Self Help Group (SHG) to students. The target participants are 36 students. The application of TKT to school children consists of 7 sessions. This activity began with the implementation of TKT session 1, namely stimulation of growth in the development of industrial aspects, session 2, namely stimulation of motor aspects, Session 3 is stimulation of cognitive and language aspects, session 4 is stimulation of emotional and personality aspects, session 5 is stimulation of moral and spiritual aspects, session 6 is stimulation of psychosocial aspects and session 7 is stimulation of all aspects from session 1 to session 6. Implementation techniques are describing, modeling, role playing, feedback, transferring. The output of this PKM activity is a scientific article published in a national community service journal accredited by Sinta 4 (Community Empowerment Journal). The target achievement is that grade III students of Pekanbaru City State Elementary School are able to carry out industrial stimulation, motor stimulation, cognitive and language stimulation, emotional and personality stimulation, moral and spiritual stimulation and psychosocial stimulation so that with this stimulation the growth and development of school-age children is normal which is needed in undergoing the educational process.